Micrometrical Studies on the Liver of Sheep during Prenatal and Postnatal Development - Choudhury, A.R. (Indian Journal of Veterinary Anatomy, 2020)
The study was conducted on liver of total 37 samples i.e. fetuses (n= 30) of 40 days’ old (2.0 cm crown anus length CAL) to postnatal sheep (n=7) below one year of age without any external anomaly to investigate the micrometrical changes during prenatal and postnatal development. The prenatal liver were divided into three groups viz. Group 1(0-50), Group 2 (51-100), Group 3 (101-150) days of gestation and Group 4 comprised of sheep below one year of age. The micrometrical observations of liver included the thickness of capsule, diameters of hepatocytes and nuclei of hepatocytes, central vein, sinusoids and haemopoietic foci and inter-central vein distance. As the age advanced a progressive increase in the thickness of capsule, diameters of hepatocytes andnuclei of hepatocytes, central vein and inter-central vein distance. Whereas, sudden increase in diameter of sinusoids of liver in the group 2 followed by slow increase in group 3 in prenatal period which again decreased during postnatal life. An increase in diameter of haemopoietic foci of liver in the group 2 followed by decrease in group 3 and in postnatal period.